Auditory affective content facilitates time-to-contact estimation of visual affective targets - Lu, Feifei; Li, You; Yang, Jiajia; Wang, Aijun; Zhang, Ming (Frontiers in Psychology, 2023)
Reacting to a moving object requires an ability to estimate when a moving object reaches its destination, also referred to as the time-to-contact (TTC) estimation. Although the TTC estimation of threatening visually moving objects is known to be underestimated, the effect of the affective content of auditory information on visual TTC estimation remains unclear. We manipulated the velocity and presentation time to investigate the TTC of a threat or non-threat target with the addition of auditory information. In the task, a visual or an audiovisual target moved from right to left and disappeared behind an occluder. Participants’ task was to estimate the TTC of the target, they needed to press a button when they thought that the target contacted a destination behind the occluder. Behaviorally, the additional auditory affective content facilitated TTC estimation; velocity was a more critical factor than presentation time in determining the audiovisual threat facilitation effect. Overall, the results indicate that exposure to auditory affective content can influence TTC estimation and that the effect of velocity on TTC estimation will provide more information than presentation time.